Long-range migratory travel of a green turtle tracked by satellite: evidence for navigational ability in the open sea - Papi, F.; Liew, H.C.; Luschi, P.; Chan, E.H. (Springer-Verlag, 1995)
A female of Chelonia mydas was tracked by satellite in the South China Sea in 1993 from the nesting beach to the resident foraging grounds more than 600 km away. The final leg of the journey, 475 km long, directly pinpointed the goal, with the turtle maintaining a constant speed and direction both night and day. This provides clues about the navigational mechanism used.